Soft Robots Manufacturing: A Review - Schmitt, François; Piccin, Olivier; Barbé, Laurent; Bayle, Bernard (Frontiers in Robotics and AI, 2018)
The growing interest in soft robots comes from the new possibilities offered by these systems to cope with problems that cannot be addressed by robots built from rigid bodies. This is in particular true when physical interaction between a robot and its environment is involved. Many innovative solutions have been developed in recent years to design soft components and systems. In this development, soft robotics has remained very closely dependent on advanced manufacturing processes, a topic which deserves special attention. This review aims at giving an insight on the current State of the Art in soft robotics, with a deeper understanding of the methods currently used to manufacture such systems.